INFORMATION TECHNOLOGIES IN ACCOUNTING AND AUDIT: PROBLEMS AND PERSPECTIVES IN THE DIGITAL ECONOMY - HEVLYCH, Larysa; HEVLYCH, Ivan (Herald of Khmelnytskyi National University. Economic sciences, 2023)
Researching the problems of digitalization of accounting and auditing in modern Ukraine is a serious scientific and practical task, considering the challenges of the post-war domestic economy and trends in the development of the accounting profession in the world. The purpose of the work is to study the current state and the nearest prospects of the use of modern information technologies in the accounting and auditing activities of Ukrainian economic entities from the point of view of identifying problems and developing ways to solve them. The work examines the requirements for modern accounting software products of domestic enterprises, highlights the financial and organizational problems of realizing the intention of automation, proposes state support measures for small and medium-sized enterprises in relation to the development of standard software with industry configurations, training of personnel domestic higher education institutions. Popular programs of foreign practice of automating the audit process were studied, TeamMate+ Audit, CaseWare IDEA, Wolters Kluwer CCH Audit Accelerator. The influence of the state of war on the domestic audit activity is identified, the main problems are highlighted and the directions for their solution are proposed through the stimulation of audit activity subjects to digitalization by state bodies and bodies of professional self-governance. The essence of modern information technologies, which are trends in the development of the accounting profession in the world, is also considered: cognitive technologies, predictive analytics, cloud platforms. Based on the results of the study, conclusions were drawn. As directions for further research, the identification of problems in the implementation of the bachelor's educational program "Digital accounting and taxation" of Vasyl’ Stus Donetsk National University from the point of view of solving the issues is proposed.
Keywords: information technology; accounting; audit; digitization